(untitled) (Doctor Virtualis, 2024)
Hildegard of Bingen interprets the whole of human life in terms of harmony and symphony: while harmony means the restoration of the relationship between humans and God and the entire redemption’s experience, the present human existence with its dangers, contradictions, and sins, corresponds to a symphony. Hildegard offers a unified vision of human beings, divine for the soul and earthly for the body. Every person is a microcosm, a multiplicity brought back to unity. The human soul is symphonialis, a characteristic expressing both the agreement between soul and body and the participation in every symphony of creation under the relationship that a person has with his or her surroundings, as well as making music.